Manipulative Influence of Visual Sources: Methodology for Identification (On The Example of The Digitazed Historical Photographs) - Yevheniia SHYSHKINA; Yaroslav MOTENKO; Oleksandr NOSYRIEV; Vasyl MALIKOV; Maryna MISHCHENKO; Leonid SAVCHENKO (Communications of International Proceedings, 2021)
The purpose of the article is to develop a methodology of the visual source study in order to identify hidden emotional and evaluative information that is transmitted through the demonstration of images. The authors of the paper focused on the searching of signs of the latent manipulative influence of photographs by means of the integrated use of historical source criticism and computer technologies. The research methodology involves the use of historical methods, methods of systems analysis and synthesis, comparison, generalization, hermeneutics, semiotics, and the application of the principles of objectivity, structure and interdisciplinary. In the article the features of source criticism of digital photographic documents are revealed as a result of integrated application of computer technologies and traditional methods of historical science. The authors come to the following conclusions: 1) the discovering of the connotative information (which can be used as a mean of manipulative social technologies) is possible only under the terms of competent study of specific historical conditions of the visual source origin; an important aspect is the identification of signs of photomontage, retouching and staged photography; 2) external and internal criticism of a digital photograph should be comprehensive and based on the use of methods of historical source studies and on verification of photos by means of digital tools and web technologies; 3) an important component of the methodology of digital photograph criticism is the use of crowdsourcing online platforms, special web services, electronic photo catalogs and digital tools; 4) the application of the methodology to the analysis of Soviet photographs of the period of Stalin’s’ dictatorship showed wide range of images with connotative information, which was found by means of historical source critique and the use of computer technologies. Methodology of identification of visual sources manipulative influence is necessary for training those professionals, who work on electronic museums, libraries, archives, reference Internet resources.
Keywords: Methodology Of Digital History; Staged Photographs; Photomontage; Palming.